Perspectives on the Passion: encountering the Bible through the arts - Joynes, Christine E.; Macky, Nancy (Library of New Testament studies, 2007)
Introduction / Christine E. Joynes -- 'Effective history' and art : a hermeneutical study with examples from the Passion narrative / Ulrich Luz -- He who hesitates is human : literary portrayals of the Gethsemane 'moment' / Peter S. Hawkins -- The Transforming power of the Cross / Timothy Gorringe -- The Passion in early Christian art / Robin M. Jensen -- From Nativity to Resurrection : musical and exegetical reasonances in the Good Friday chants Domine Audiui and Qui Habitat / Emma Hornby -- In Persona Mariae : singing the Song of Songs as a Passion commentary / William T. Flynn -- Emblem and irony : Passion narrative in post-Reformation hymnody / J. R. Watson -- Christian cannibalism and human(e) sacrifice : the Passion in the conversion of the Aztecs / Jaime Lara -- The Mass and te theatre : sacrifice and murder in Othello / Regina M. Schwartz -- Bad Friday / Sara Maitland -- Afterword / Nancy Macky